Indonesia and South Korea Business Competition Laws in The Investment Sector - Asmah; Pasanda, Danil (UNES Law Review, 2025)
Business activities carried out by business actors in the investment sector can have a competitive effect that can affect the economy, especially in Indonesia and South Korea. The concept of economy in Indonesia by advancing the idea of democracy with various policies and regulations issued by the government, such as policies in the field of business competition. The Indonesian government issued Law No. 5 of 1999 prohibiting unfair business practices and competition to promote the people's welfare, create fair competition and facilitate investors in doing business. That thing is based on the principle of justice in business. However, on the side, On the other hand, South Korea has the Regulation and Fair Trade Act that provides fair business and investment opportunities. This study uses a normative juridical research method using secondary data, which will then be analyzed using qualitative methods with deductive conclusions. This study concludes that the comparison of business competition law between Indonesia and South Korea implements a legal system of justice and investment opportunities with no restrictions. Both countries, with their legal and government systems, have specific policies and rules, so there are differences: Indonesia with civil law, and South Korea with civil law Inquisitorial. In regulating business competition and investment, Indonesia prioritizes foreign investors' rules and investment periods, while South Korea focuses more on income for the country's prosperity